2022
DOI: 10.1136/bmjopen-2021-057906
|View full text |Cite
|
Sign up to set email alerts
|

Active monitoring versus immediate abduction as treatment of stable developmental dysplasia of the hip: a systematic review of the literature

Abstract: ObjectivesThis systematic review aims to compare the effects of active monitoring and abduction treatment on the Graf alpha angle, Acetabular Index (AI) and femoral head coverage in infants with stable developmental dysplasia of the hip (DDH).DesignSystematic review reported according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines.Data sourcesA search of the PubMed, Embase, Cochrane and Web of Science databases was performed in January 2020 and updated in January 2021.Elig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…A few studies have compared active monitoring and abduction treatment for infants with centered DDH [ 10 15 ]. A recent review summarizes that there is no difference in acetabular index between active monitoring and abduction treatment for infants up to four months of age with centered DDH after three months [ 16 ]. However, the included six studies showed considerable methodological heterogeneity and two non-randomized studies were rated as serious risk of bias.…”
Section: Introductionmentioning
confidence: 99%
“…A few studies have compared active monitoring and abduction treatment for infants with centered DDH [ 10 15 ]. A recent review summarizes that there is no difference in acetabular index between active monitoring and abduction treatment for infants up to four months of age with centered DDH after three months [ 16 ]. However, the included six studies showed considerable methodological heterogeneity and two non-randomized studies were rated as serious risk of bias.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] With mild DDH, previous studies suggest that observation period of four to six weeks is safe, as many of these children recover spontaneously 8,16 . It is also known that stable, but dysplastic hips do not require abduction treatment 17 . There are several studies around the subject of abduction treatment failure and some risk factors associated to treatment failure have been found.…”
Section: Introductionmentioning
confidence: 99%